A study on screening for scoliosis among school children in the age group of 10-14 using a cost effective and an innovative technique - Talasila, Sai Sri Akshara; Gorantla, Misha; Thomas, Vimala (International Journal Of Community Medicine And Public Health, 2017)
Background: Scoliosis refers to a sideways curvature of the spine. Early detection of scoliosis prevents progress into severe scoliosis. In a resource constrained setting like India, there is a need for cost effective solutions for the purpose of screening. Objective of this study is to identify scoliosis among school children, determine risk factors associated with scoliosis and to compare the readings of the Scoliometer device to those obtained from Scoliometer smartphone app. Methods: The present cross sectional study was conducted in students aged 10-14 years studying in private schools of Hyderabad. All willing students (n=1000) were screened for scoliosis during June-August 2015. They were screened using physical examination (Adams forward bend test), Scoliometer device and Scoliometer App. Results: A total of 3.3% of the students had positive scoliosis findings when physically examined in standing position and 3.4% were positive for Adam’s forward bend test. Around 0.7% of students had a reading >7o when screened using the Scoliometer device and 1% had a reading >7o when screened using the App i.e. similar results were obtained. The risk factors associated with scoliosis found by this study includes prematurity of foetus during delivery and carrying school bag on one shoulder which had statistically significant association with positive scoliotic findings with O.R of 3.6 and 4.3 at 95% CI respectively. Conclusions: Scoliometer app can replace the expensive Scoliometer device for screening of scoliosis. This can be included in school health programmes.